2015
DOI: 10.1007/s00737-014-0495-7
|View full text |Cite
|
Sign up to set email alerts
|

Health services utilization of women following a traumatic birth

Abstract: This cohort study compared 262 women with high childbirth distress to 138 non-distressed women. At 12 months, high distress women had lower health-related quality of life compared to non-distressed women (EuroQol five-dimensional (EQ-5D) scale 0.90 vs. 0.93, p = 0.008), more visits to general practitioners (3.5 vs. 2.6, p = 0.002) and utilized more additional services (e.g. maternal health clinics), with no differences for infants. Childbirth distress has lasting adverse health effects for mothers and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…, Dennis ) and following traumatic birth (Turkstra et al . ). HVs described that anxious women worried more about their baby's development and care taking which might suggest an increased need for reassurance in these women.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Dennis ) and following traumatic birth (Turkstra et al . ). HVs described that anxious women worried more about their baby's development and care taking which might suggest an increased need for reassurance in these women.…”
Section: Discussionmentioning
confidence: 97%
“…In the general population, anxiety has been associated with increased healthcare service usage (Shapiro 1984, de Beurs et al 1999, Fleury et al 2014. So far, healthcare utilisation of women with postpartum anxiety has not been investigated, but previous studies have demonstrated an increased level of healthcare service utilisation among women with postpartum depression (Webster et al 2001, Dennis 2004) and following traumatic birth (Turkstra et al 2015). HVs described that anxious women worried more about their baby's development and care taking which might suggest an increased need for reassurance in these women.…”
Section: Service Usagementioning
confidence: 99%
“…Health-related quality of life is measured with the EQ-5D-5L, a generic instrument that was developed by the EuroQol Group [ 49 51 ]. The internal consistency is good (Cronbach’s alpha of 0.83).…”
Section: Interventionmentioning
confidence: 99%
“…Childbirth is one of the most challenging psychological events in a mother’s life, as 10–34% of all childbearing women are faced with traumatic birth experiences [ 1 , 2 ]. A negative experience in childbirth is associated with post-traumatic stress disorder (PTSD), disruption to interpersonal relationships, dysfunctional maternal-infancy bonding [ 3 5 ], reduction in rates of exclusive breastfeeding [ 6 ], inappropriate utilization of maternal and newborn care services [ 7 ], fear of childbirth and increased desire for an elective caesarean section in future pregnancies [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%